2016
DOI: 10.1111/cid.12426
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Maxillary Sinus Lateral Wall and Posterior Superior Alveolar Artery Anatomy: A Cone‐Beam Computed Tomographic Study

Abstract: The results from this study suggest that using CBCT prior to the surgery provides valuable diagnostic information. However, undetected intraosseous canal in CBCT does not exclude its existence. Alteration in the lateral window design and the use of piezoelectric instruments are recommended if intraoperative complications are expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 37 publications
16
60
1
Order By: Relevance
“…In contrast to the findings of Li et al 12 and in agreement with several previous studies, 15,19,32,33,34 this study found that gender does not affect the thickness of the buccofacial maxillary sinus wall. The authors also found that the age of the patients was not a confounding factor affecting the thickness of the buccofacial maxillary sinus wall, again in contrast to the results reported by Li et al 12 and Monje et al 15 Monje et al 15 reported that maxillary sinus wall thickness was directly proportional to patient age, whereas Li et al 12 found an influence of age in the region of the molars.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In contrast to the findings of Li et al 12 and in agreement with several previous studies, 15,19,32,33,34 this study found that gender does not affect the thickness of the buccofacial maxillary sinus wall. The authors also found that the age of the patients was not a confounding factor affecting the thickness of the buccofacial maxillary sinus wall, again in contrast to the results reported by Li et al 12 and Monje et al 15 Monje et al 15 reported that maxillary sinus wall thickness was directly proportional to patient age, whereas Li et al 12 found an influence of age in the region of the molars.…”
Section: Discussionsupporting
confidence: 90%
“…14,15 In contrast, in a study of 74 non-embalmed Korean hemifaces, Yang et al 13 reported that the buccofacial wall was thinner in the second molar region than in the first molar region, in agreement with the current findings. A similar observation was recently reported by Danesh-Sani et al 19 Surprisingly, Li et al 12 found that the buccofacial wall gradually became thinner from the region of the second premolar towards the region of the second molar, 5 mm from the floor of the sinus. This observation is consistent with our findings for all 3 ethnic groups in this study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations